FACTORS AFFECTING THE SURVIVAL OF MICRO, SMALL AND MEDIUM ENTERPRISES IN KAKAS DISTRICT - Sigar, Frista R.; Lapian, Joyce S. L. H. V.; Saerang, Regina T. (Universitas Sam Ratulangi, 2022)
Micro, Small and Medium Enterprises (MSMEs) is one type of business that continues to grow from year to year. With the type of development and needs that continue to increase, it is certain that the number of MSMEs will continue to increase in the coming years. With the efficiency and prominence of the MSME trend, of course this is a good path for people who want to open a business and pursue this new type of business. However, the fact that MSMEs have this advantage opens up opportunities for everyone, thus creating intense competition with each other. The purpose of this study was to analyze the factors affecting the survival of Micro, Small and Medium Entrepreneurship in Kakas District. Researchers do this research through quantitative methods using Multiple Regression Analysis (MLR) as an analytical tool. To achieve this goal, the researchers distributed questionnaires and the sample used was 50 respondents from Micro, Small and Medium Enterprises owners in Kakas District. Keywords: micro, small and medium enterprises, survival of MSMEs